COMMUNITY SENSE OF COHERENCE AMONG ADOLESCENTS AS RELATED TO THEIR INVOLVEMENT IN RISK BEHAVIORS. Issue 1 (January 2016) - Elfassi, Yamit; Braun‐Lewensohn, Orna; Krumer‐Nevo, Michal; Sagy, Shifra
Abstract : The current study employs a new concept–community sense of coherence (CSOC)–that measures youth's perceptions of their own community and its potential as a source for protective factors and assets. The theoretical foundation for this measure is the salutogenic approach and its concept of "sense of coherence." A total of 1023 students from the 8th to 11th grades, living in 3 Israeli communities, filled out self‐reported questionnaires that included measures of CSOC and involvement in risk behaviors. Results indicated significant negative correlations between CSOC and the levels of risk behaviors. The overall variance of risk behaviors explained by CSOC was found to be different in each of the three communities. The findings suggest that CSOC is a significant protective factor that could be related to reduced involvement in risk behaviors. The results are discussed within the framework of community protective factors and the salutogenic approach.